SOCIAL AND RELIGIOUS DYNAMICS OF THE COMMUNITY IN THE GUNUNG EMBUN TOURIST AREA, PASER REGENCY - Amirullah, Amirullah (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2025)
This study aims to describe the religious and social dynamics of the community in Luan Village, located in the Gunung Embun tourist area, Paser Regency. The focus of the study includes values and beliefs, religious practices, social interactions, and social changes that have occurred due to the influence of tourism. The method used is descriptive qualitative with techniques of interviews, observation, and documentation, as well as data analysis using the Miles, Huberman, and Saldana model with stages of data condensation, data presentation, and conclusion drawing and verification. The results of the study show that the people of Luan Village combine Islamic values with local traditions, practice religious and traditional activities side by side, and maintain social interaction through mutual cooperation. The presence of Gunung Embun tourism has a positive impact in the form of economic opportunities and social mobility, but also has the potential to influence local culture.